2004
DOI: 10.1111/j.1368-5031.2004.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pioglitazone on the components of diabetic dyslipidaemia: Results of double-blind, multicentre, randomised studies

Abstract: A total of 3,713 patients with poorly controlled type 2 diabetes were enroled into four multicentre, double-blind studies and randomised to receive pioglitazone, sulphonylurea, metformin or a combination of two of these agents for up to 52 weeks. Data from patients with a lipid evaluation, at week 52, were pooled, and treatment groups were compared using analysis of covariance. Pioglitazone, alone or combined with metformin or sulphonylurea, resulted in mean decreases in triglycerides (-9 to -11%), total/HDL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
(19 reference statements)
2
11
1
Order By: Relevance
“…A similar result was found in a trial of TROG added to failed therapy with metformin plus sulfonylurea treatment [8]. Compared with sulfonylurea or metformin treatment, which reduced LDL cholesterol by 3.5% and 0.6% from baseline, respectively, PIO increased LDL cholesterol by 8.4% [13]. In dose-ranging studies, there did not seem to be a dose-dependent response and the effect appeared to be additive when PIO was added to other antihyperglycemic therapy [3,4,[12][13][14][15][16][17].…”
Section: Clinical Trialssupporting
confidence: 68%
See 2 more Smart Citations
“…A similar result was found in a trial of TROG added to failed therapy with metformin plus sulfonylurea treatment [8]. Compared with sulfonylurea or metformin treatment, which reduced LDL cholesterol by 3.5% and 0.6% from baseline, respectively, PIO increased LDL cholesterol by 8.4% [13]. In dose-ranging studies, there did not seem to be a dose-dependent response and the effect appeared to be additive when PIO was added to other antihyperglycemic therapy [3,4,[12][13][14][15][16][17].…”
Section: Clinical Trialssupporting
confidence: 68%
“…Compared with sulfonylurea or metformin treatment, which reduced LDL cholesterol by 3.5% and 0.6% from baseline, respectively, PIO increased LDL cholesterol by 8.4% [13]. In dose-ranging studies, there did not seem to be a dose-dependent response and the effect appeared to be additive when PIO was added to other antihyperglycemic therapy [3,4,[12][13][14][15][16][17]. There may be a time-related attenuation of the LDL-raising effect because there was no significant increase in LDL cholesterol in the PIO-treated group of the 3-year PROactive trial [18].…”
Section: Clinical Trialsmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, reduction of these atherogenic parameters by the agent might be beneficial for the prevention of atherosclerosis, including CHD, due to its anti-inflammatory effect, in diabetic patients. However, different from other reported studies [22][23][24] , we could not observe any significant change in other parameters, including TG, T-Cho, LDL-C, HDL-C, leptin, or adiponectin, although the value of TG decreased to 73% ( Fig. 2A) and that of adiponectin increased to 162.8% at the end of the study (Table 2).…”
Section: Discussioncontrasting
confidence: 55%
“…Recent intervention trials have shown that insulin-sensitizing agents, including metformin and other TZDs, affect dyslipidemia [22][23][24] and the abnormal secretion of adipocytokines, such as adiponectin 25,26) , in diabetic patients; however, whether insulin-sensitizing agents such as pioglitazone could affect the levels of these potential risk factors for diabetic macroangiopathy remains undetermined.…”
Section: Discussionmentioning
confidence: 99%